2015
DOI: 10.3892/mco.2015.555
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar epoetin α is as effective as originator epoetin-α plus liposomal iron (Sideral®), vitamin B12 and folates in patients with refractory anemia: A retrospective real-life approach

Abstract: Abstract. Several biosimilar versions of recombinant human erythropoietin are currently approved for use in Europe, including a biosimilar epoetin-α. The aim of this the study was to verify that biosimilar epoetin-α is similar in terms of efficacy, safety and cost to originator epoetin-α for the treatment of refractory anemia in patients with myelodysplastic syndrome. A total of 92 patients with myelodysplasia and refractory anemia were investigated. The patients received either originator (group A) or biosimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…An observational study by Giordano et al [39] on sucrosomial iron in patients with sideropenic anemia confirmed the reduction of the typical side effects of a conventional martial treatment, determining at the same time an improvement of the patient’s anemic condition in terms of serum iron, Hb, and ferritin [24, 25, 39]. Another study by Pisani et al [27] in patients with chronic kidney disease demonstrated the non-inferiority of the oral sucrosomial iron compared to IV iron therapy in terms of increase in Hb levels.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study by Giordano et al [39] on sucrosomial iron in patients with sideropenic anemia confirmed the reduction of the typical side effects of a conventional martial treatment, determining at the same time an improvement of the patient’s anemic condition in terms of serum iron, Hb, and ferritin [24, 25, 39]. Another study by Pisani et al [27] in patients with chronic kidney disease demonstrated the non-inferiority of the oral sucrosomial iron compared to IV iron therapy in terms of increase in Hb levels.…”
Section: Discussionmentioning
confidence: 99%
“…The only RCT in patients with cancer 30 had a high likelihood of bias based on inadequate sample size, lack of an intent-to-treat analysis, and industry funding and authorship. The quality of the four included cohort studies of biosimilars [31][32][33][34] in patients with cancer was not formally assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review of biosimilar ESAs included two metaanalyses 27,28 and one RCT 29 in patients with CKD, and one RCT 30 and three cohort studies [31][32][33] in patients with cancer. In a 2017 meta-analysis of RCTs in CKD, Amato et al 27 reported that efficacy and safety outcomes did not differ significantly between patients treated with epoetin alfa originator or biosimilar but described the quality of evidence as low to very low.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent studies we successfully used liposomal iron (Sideral ® Pharmanutra), a new generation iron (ferric phosphate) supplement containing phospholipids and sucrose esters of fatty acids assuring its high bioavailability and tolerability [81]. The efficacy of this drug in correcting iron deficiency attested by the restoration of physiological hemoglobin levels has been proven in human and animal studies [82,83]. We show that liposomal iron given orally to suckling piglets is a suitable feed additive for the reinforcement of iron status in piglets in the critical period from birth to weaning.…”
Section: Oral Supplementationmentioning
confidence: 99%